2000
DOI: 10.1063/1.481654
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical study of valence photoelectron spectrum of OsO4: A spin-orbit RESC-CASPT2 study

Abstract: Articles you may be interested inStrong electron correlation in UO2 −: A photoelectron spectroscopy and relativistic quantum chemistry study J. Chem. Phys. 140, 094306 (2014); 10.1063/1.4867278 Closed-shell coupled-cluster theory with spin-orbit coupling J. Chem. Phys. 129, 064113 (2008); 10.1063/1.2968136 Spin-orbit configuration interaction study of the electronic structure of the 5 f 2 manifold of U 4 + and the 5 f manifold of U 5 + J. Chem. Phys. 128, 154310 (2008); 10.1063/1.2888560High-order electron-cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
1

Year Published

2001
2001
2009
2009

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 28 publications
0
16
1
Order By: Relevance
“…To further confirm this finding, we performed a two‐step calculation: After the scalar relativistic SCF calculation converged, the SOC matrix was constructed and diagonalized without further iterations. The so obtained energy levels of the relevant spinors differ by less than 0.05 eV from those by the variational calculation, clearly indicating that the inadequate treatment of the SOC in Ref 24. is due to the chosen empirical one‐electron spin‐orbit operator rather than the state interaction approach.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…To further confirm this finding, we performed a two‐step calculation: After the scalar relativistic SCF calculation converged, the SOC matrix was constructed and diagonalized without further iterations. The so obtained energy levels of the relevant spinors differ by less than 0.05 eV from those by the variational calculation, clearly indicating that the inadequate treatment of the SOC in Ref 24. is due to the chosen empirical one‐electron spin‐orbit operator rather than the state interaction approach.…”
Section: Resultsmentioning
confidence: 87%
“…Several relativistic calculations have been carried out at both ab initio 5, 10, 24 and density functional11, 25–28 levels of theory. However, the SOC effects were either neglected completely5, 10, 11, 28 or treated inadequately by using an empirically scaled one‐electron spin‐orbit operator 24. The source for the SOC has been disputed26, 27 when interpreting the PE spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…The code in GAMESS, 17 which we have used, goes back to Nakajima and Hirao 24 and Nakajima et al 25 and was further modified by Fedorov et al 26 Earlier studies 21 of diatomic binding energies had indicated that CASSCF calculations using cc-pVQZ bases yield satisfactory scalar relativistic contributions. To assess the reliability of this choice, we made DK3 calculations with a number of wavefunctions at selected points along the dissociation curve.…”
Section: B Scalar Relativistic Energy Contributionsmentioning
confidence: 99%
“…The RESC approach has been applied to various systems in ground and excited states. [106][107][108][109][110][111][112][113] RESC has been known to work well for a number of systems, and recent studies show that RESC gives similar results for the chemical properties as the DKH method, although very large exponents in the basis set can lead to variational collapse in a current RESC approximation, partly because the current implementation includes only the lowest truncation of the O operator. Since the energy gradient of the RESC method is also available currently, 114 we can study the chemical reaction in the heavy element systems.…”
Section: Resc Methodsmentioning
confidence: 99%